Perancngan dan Impelementasi Website Profil Polsek Kota Kisaran Sebagai Media Informasi Publik - Widia Triana Sagala; Intan Nur Ilani; Rindi Anita; Ewit Diangsi (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
The development of information technology requires public institutions to provide accessible and transparent information services. Polsek Kota Kisaran still faces limitations in delivering information to the public through digital media. This study aims to design and implement a profile website as a public information medium that supports service transparency. The research uses a qualitative descriptive approach with data collection through observation, informal interviews with police officers, and documentation. System development includes requirement analysis, system modeling using Unified Modeling Language (UML), interface design, and website implementation. The results indicate that the developed website is able to present structured information such as institutional profiles, organizational structures, SKCK procedures, SPKT services, news, and activity documentation. The implementation of this website facilitates public access to police information and improves the effectiveness of information dissemination. This study is expected to support digital-based public services at the local police level and strengthen public trust through transparent information delivery.